2019
DOI: 10.1371/journal.ppat.1008064
|View full text |Cite
|
Sign up to set email alerts
|

IgG3 enhances neutralization potency and Fc effector function of an HIV V2-specific broadly neutralizing antibody

Abstract: Broadly neutralizing antibodies (bNAbs) protect against HIV infection in non-human primates and their efficacy may be enhanced through interaction with Fc receptors on immune cells. Antibody isotype is a modulator of this binding with the IgG3 subclass mediating potent Fc effector function and is associated with HIV vaccine efficacy and HIV control. BNAb functions are typically assessed independently of the constant region with which they are naturally expressed. To examine the role of natural isotype in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
99
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 71 publications
17
99
2
Order By: Relevance
“…These phenotypes were consistent at varying ratios of effector cells and target particles, whether cell lines or primary phagocytes were used as effectors, and whether fluorescent antigen beads or viral particles were used as targets. The direct relationship between hinge length and phagocytosis may also hold for other specificities, as Richardson et al now also demonstrate for CAP256 [89]. Collectively, this data points toward hinge modification as an additional tool for antibody engineering, and provides a new rationale to investigate IgG3 responses and allotypic variation in hinge length in the context of cohort studies.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These phenotypes were consistent at varying ratios of effector cells and target particles, whether cell lines or primary phagocytes were used as effectors, and whether fluorescent antigen beads or viral particles were used as targets. The direct relationship between hinge length and phagocytosis may also hold for other specificities, as Richardson et al now also demonstrate for CAP256 [89]. Collectively, this data points toward hinge modification as an additional tool for antibody engineering, and provides a new rationale to investigate IgG3 responses and allotypic variation in hinge length in the context of cohort studies.…”
Section: Discussionmentioning
confidence: 55%
“…We found that the neutralization activity of VRC01 and 447-52D were not altered by hinge length. However, Richardson et al find a modest but reproducible effect on the neutralization potency of CAP256 results from hinge modification [89]. Collectively, these data suggest that the impact of hinge composition varies across both different antibodies as well as across different viruses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…IgG3 form of 1E5 showed better reactivity than the IgG1 form Recent reports described the superior nature of the IgG3 class over IgG1 not only for Fc-receptor-mediated functions, such as ADCC and ADCP, but also for neutralization capability (21,(23)(24)(25)(26)(27). To obtain 1E5 with superior activities, we constructed an IgG3 form of 1E5 in addition to the IgG1 form.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have described the superior nature of the IgG3 class of antibodies over the IgG1 class, not only for Fc-receptor-mediated functions, such as ADCC and antibody-dependent cellular phagocytosis (ADCP) (21,(23)(24)(25)(26)(27), but also for their neutralization capability (26). The level of IgG3 correlated with anti-HIV-1 function in the RV-144 trial (28,29) and was involved in the control of disease in different cohorts (21,30).…”
mentioning
confidence: 99%